2015
DOI: 10.5194/se-6-573-2015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid revegetation by sowing seed mixtures of shrub and herbaceous species

Abstract: Abstract. Fast revegetation by means of sowing seed mixtures of shrub and herbaceous species is a measure to prevent bare soils from wind and water erosion. A field experiment was used to test the effect of species selection and the ratio of shrub to herbaceous species on vegetation formation and shrub growth. Results showed that herbaceous species hastened cover formation and maintained a high coverage for a longer period. However, the growth of shrubs was hindered. In the North China Plain or where the soil … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Land degradation has received considerable interest from academic scholars and governments, mainly paying attention to issues of desertification and deserts as fragile ecosystems, the loss of forest lands, and environmental changes in scrublands (Vieira et al , ; Easdale, ; Keesstra et al , ; Lucas‐Borja et al , ). However, grasslands also play an important role in global ecosystems, and grassland degradation therefore deserves further attention (Feng et al , ; Hu et al , ; Mekonnen et al , )…”
Section: Introductionmentioning
confidence: 99%
“…Land degradation has received considerable interest from academic scholars and governments, mainly paying attention to issues of desertification and deserts as fragile ecosystems, the loss of forest lands, and environmental changes in scrublands (Vieira et al , ; Easdale, ; Keesstra et al , ; Lucas‐Borja et al , ). However, grasslands also play an important role in global ecosystems, and grassland degradation therefore deserves further attention (Feng et al , ; Hu et al , ; Mekonnen et al , )…”
Section: Introductionmentioning
confidence: 99%
“…The soil seed distribution in the different locations around the cushions can also be used as a tracer of the seed redistribution (Cerdà & García‐Fayos, ; De Vlaeminck et al, ; Yu et al, ) and help to understand the seed behaviour (Wang et al, ). Moreover, understanding the fate of the seeds along the slopes is definitive to plan restoration and rehabilitation programmes (Feng et al, ; Gilardelli et al, ; Qian et al, ). In fact, the plant patches and their interaction with the sediment, water movement and seeds redistribution is a well‐known issue (Cerdà, ; Akhtar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al . () found that rapid revegetation could be obtained in the North China Plain by sowing seed mixtures of shrub and herbaceous species, and it is a useful measure to protect soil from wind and water erosion. Tian et al .…”
Section: Introductionmentioning
confidence: 99%